Cross Border Security Challenges for Bangladesh: A Thematic Analysis - Husain, Taha (Society & Sustainability, 2024)
This study aims to explore the challenges of cross-border security in Bangladesh. Employing a qualitative methodology, the study gathers insights from diverse stakeholders, including security forces, analysts, human rights activists, NGO workers, and journalists. Based on thematic analysis, the findings revealed a significant disconnect between the Border Guard Bangladesh (BGB) and local communities, exacerbated by bureaucratic challenges and poor coordination among governmental bodies. The vulnerability of hilly border regions to illicit activities, such as insurgency and smuggling, is heightened by inadequate placement and density of Border Outposts (BOPs). Historical and cultural ties influence border dynamics, complicating security efforts. The BGB faces infrastructure and resource challenges, further hampering effective border management. Extreme poverty and lack of education in border communities drive individuals towards smuggling and make them susceptible to human trafficking. Cross-border criminal activities, including drug and arms trafficking, pose significant threats. Additionally, the influx of Rohingya refugees has led to the control of refugee camps by armed groups, creating further security concerns. This research's originality lies in its thematic analysis application to systematically explore and address the multifaceted cross-border security challenges in Bangladesh.